A groupware to support multi-user communication with a network whiteBoard (CommunityBoard) / Leong Sook Yuen - Leong , Sook Yuen (2005)
Collaboration of distributed workgroup needs group management tools to maintain their own workgroup. The definition of group managements here is restricted to methods of group working rather than simply communicating. For example, working together on documents or sharing application such as whiteboard. Thus, we are looking for a way to having effective communication between each member in the workgroup and an accomplished mature group management tools to internet users. Nowadays, many of the new collaboration tools are provided on a server and accessed with a web browser. Some are also available using browser plug-ins, or using special purpose client software. This project steps towards developing a groupware which can support multi-users communication with a network whiteboard. The main aspect of this project is to produce a white-board system which processed multiple whiteboard session s or groups concurrently, enabling users to communicate with people over the internet via a graphical whiteboard. It provides a powerful mechanism for group management distance learning and other areas of application. In conclusion, this project integrating group management tools and the whiteboard tools to producing effectively multimedia web-based application.